A numerical study of intake valve jet flapping in a gasoline direct injection engine. (2018) - Beavis, Nicholas J.; Ibrahim, Salah S.; Malalasekera, Weeratunge
This paper presents findings from a numerical study of intake valve jet flapping within a gasoline direct injection (GDI) engine, using a large eddy simulation (LES) turbulence modelling approach. The experimental test case and computational setup, including choice of sub-grid scale (SGS) turbulence model, are presented and discussed. An example cycle where intake valve jet flapping is seen to be prominent is discussed in detail. Intake valve jet flapping was found to be initiated as a consequence of turbulent fluctuations in the intake valve curtains. Cycle-by-cycle variations in valve curtain mass flux and the subsequent jet flapping events are investigated and significant cyclic variability is found. It was observed that when an ensemble-averaging procedure, typically used in LES simulations and experimental PIV data post-processing, is applied, due to the cyclic variability of the variations in valve curtain mass flux, most of the information related to this flow phenomenon is lost.